Forest Soil Carbon Stock along an Altitudinal Gradient in Darjeeling Himalayan Region - Banerjee, S. K. (Indian Forester, 2014)
Carbon stock in soils results from the balance between inputs and outputs of carbon within the below ground environment and the amount of soil organic carbon and its rate of decomposition varies with temperature and precipitation. Altitude is often included in the studies of climate variables on soil organic carbon dynamics. Present study was undertaken to assess the soil organic carbon stock along an altitudinal gradient from 155 to 3500 m amsl in Darjeeling Himalayan region only under foliage cover. Maximum soil organic carbon in the top soil layer (0 - 15cm) was exhibited by sub-alpine/alpine and high altitude (2500 - 3500m and 2000 - 2500m respectively) forest sites (59.8 and 58.2 g/kg respectively) followed by mid-altitude (1500 - 2000 m) forest sites (46.1 g/kg), lower hill (1000 - 1500m) forest sites (40.3 g/kg) and low altitude (500 - 1000 m) forest site (35.8 g/kg). In the Tarai region (<500m), the value was still less (26.9 g/kg). A decreasing trend in soil organic carbon was observed with increased soil depth.